Lifelong Learning and Education in Healthy and Sustainable Cities - Walter Leal Filho (Berlin ; Springer International Publishing, 2018)
This book presents essential insights into lifelong learning and education in healthy and sustainable cities, providing a basis for strategies to help achieve the 2030 Agenda sustainable development and health promotion goals. The interface between environment, health and lifelong learning is fundamental to attaining these goals, and as such, the book gathers interdisciplinary reflections from researchers, educators and other experts concerning the links between environmental quality, human health, human education and well-being, and addressing inequality, unplanned urbanization, migration, lifestyles, and consumption and production patterns. Topics include: Urban planning to address inequality in health and urban poverty; Healthy cities and healthy environments; Governance for sustainable development; Social determinants of health oriented on sustainable development goals; Education and lifelong learning for sustainability; Energy security, access and efficiency; Sustainable cities, buildings and infrastructure.